From solutions to porous film: Influence of the media on fluorescent acridine end-capped polystyrene photophysic properties. (June 2015) - Said, Ali; Karaky, Khaled; Chreim, Yamama; Brown, Ross; Blanc, Sylvie; Lacombe, Sylvie; Save, Maud; Billon, Laurent
Graphical abstract: Abstract: Nitroxide-mediated radical polymerization (NMP) was used to synthesize polystyrene (PS) in the presence of N-tert-butyl-N-(1-diethylphosphono-2, 2-dimethylpropyl)nitroxide (SG1) as a control agent and the BlocBuilder ® alkoxyamine as an initiator. The α -telechelic carboxylic acid PS was further functionalized by the fluorescent 9-aminoacridine moiety (9AA) to synthesize α -functional fluorescent polystyrene (PS-9AA). The 9-aminoacridine end-capped PS was characterized by size exclusion chromatography, two dimensional heteronuclear multiple-bond correlation nuclear magnetic resonance and fluorescence spectroscopy. The PS-9AA α -telechelic polymer was used to prepare fluorescent continuous and porous polymer films via the Breath Figure (BF) method. The fluorescence properties of PS-9AA in solution were compared to the corresponding one in the continuous and porous polymer films.